Antimony as a programmable element in integrated nanophotonics - Aggarwal, Samarth; Milne, Tara; Farmakidis, Nikolaos; Feldmann, Johannes; Li, Xuan; Shu, Yu; Cheng, Zengguang; Salinga, Martin; Pernice, Wolfram; Bhaskaran, Harish (Nano letters, 2022)
The use of nonlinear elements with memory as photonic computing components has seen a huge surge in interest in recent years with the rise of artificial intelligence and machine learning. A key component is the nonlinear element itself. A class of materials known as phase change materials has been extensively used to demonstrate the viability of such computing. However, such materials continue to have relatively slow switching speeds, and issues with cyclability related to phase segregation of phase change alloys. Here, using antimony (Sb) thin films with thicknesses less than 5 nm we demonstrate reversible, ultrafast switching on an integrated photonic platform with retention time of tens of seconds. We use subpicosecond pulses, the shortest used to switch such elements, to program seven distinct memory levels. This portends their use in ultrafast nanophotonic applications ranging from nanophotonic beam steerers to nanoscale integrated elements for photonic computing.
Gesehen am 13.07.2022